The Importance of Supply Chain Management Practices in Increasing Customer Satisfaction and Customer Retention: Evidence from Saudi Arabia - Ahmed, Abdullah (International Journal of Scientific Research and Management (IJSRM), 2021)
This study sought to determine the effects of supply chain management practices on customer satisfaction and retention in major retails food companies located in Southern Region of Saudi Arabia. Data collection was done by survey using questionnaire. The number of samples is 208 employees, with the method of convenient sampling. The method of analysis in this study is the multiple linear regression analysis, with SSPS testing reliability and normality, correlation, hypothesis testing, simultaneous effect and the coefficient of determination.  The results find a statistically significant and positive relationship between strategic supplier partnership (SSP), customer relationship (CR), Level of information sharing (LIS), level of information quality (LIQ) postponement practice (PP) and customer satisfaction (CS). However, the relationship between Customer Relationship (CR) and customer satisfaction (CS) is considered statistically non-significant and negative. Furthermore, customer satisfaction (CS) is a good predictors of customer retention (CRe).  This finding can be used implementatively for management to improve the elements supporting the strengthening of supply chain management practices and increasing customer satisfaction and retention in the retail food companies. Nonetheless, the findings of the study help companies to improve the quality of their services, products, and treat customers as their first priority in order to be retained them. Therefore, theses guide customers to recommend the firms to others. The results identify the influence of supply chain management practices on the customer satisfaction and retention according to the food retail sector in Saudi Arabia.